2018
DOI: 10.1021/acs.jpcc.7b11102
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Thermally Activated Hydrocarbon Dehydrogenation on the Pt3Ni(111) Surface: From Adsorbed Hydrocarbons up to Graphene Formation

Abstract: The Pt 3 Ni(111) alloy is characterized by the presence of an outermost surface layer only composed by Pt atoms, that is, the so-called Pt skin, which is at the basis of its outstanding performances in oxygen reduction reaction. The growth of graphene on this alloy is further motivated by the realization of a charge-neutral Gr/metal gate, which can be replaced by a p-doped Gr/oxide/metal configuration upon heating in an oxygen environment. Herein, we have followed the complete reaction pathway starting with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The concept of correlating AP-XPS data to the kinetics of carbon growth on the exposure scale has been successfully exploited in the context of graphene growth on model materials. 16,17,50 In comparison, our work introduces this concept to the eld of the precise kinetic characterization of catalytic reactions. To fully appreciate the possibilities entailed by a fully quantitative data alignment, it should be emphasized that TAP offers a detailed view of reaction kinetics at several temporal scalesfrom sub-second differences in the mean residence times of species, through several seconds within each pulse, to the accumulated changes over hundreds of pulsesand all these characteristics could be related to the surfacesensitive spectral features probed by XPS for cases of technological and fundamental importance.…”
Section: A Common Exposure Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The concept of correlating AP-XPS data to the kinetics of carbon growth on the exposure scale has been successfully exploited in the context of graphene growth on model materials. 16,17,50 In comparison, our work introduces this concept to the eld of the precise kinetic characterization of catalytic reactions. To fully appreciate the possibilities entailed by a fully quantitative data alignment, it should be emphasized that TAP offers a detailed view of reaction kinetics at several temporal scalesfrom sub-second differences in the mean residence times of species, through several seconds within each pulse, to the accumulated changes over hundreds of pulsesand all these characteristics could be related to the surfacesensitive spectral features probed by XPS for cases of technological and fundamental importance.…”
Section: A Common Exposure Scalementioning
confidence: 99%
“…[41][42][43][44][45][46][47][48] More recently, an ALD-derived PtIn catalyst was reported that achieved unprecedented catalytic performance by combining propane dehydrogenation with selective hydrogen combustion. 49 Although time-resolved XPS studies have been extensively reported for similar (single crystal) model materials, 16,17,50 our ndings provide the rst example in which AP-XPS and TAP data were evaluated on nanoscopically-equivalent, triplecomponent (Pt, In, and MgO) ALD model materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the grown graphene was heated in an oxygen environment, Ni atoms segregated toward the surface followed by being oxidized to an oxide layer containing Ni . This process converted the graphene/metal configuration to the graphene/metal oxide/metal configuration, which might have important significance in the field of electronic devices. , In brief, the dual-element alloy single-crystal plane can not only keep the orientation of graphene growth but also achieve the layer number control by adjusting the atomic ratios of different metals in the alloy. Owing to the unique dual-element and single-crystal plane characteristics of the single-crystal binary alloys, those alloys have great potential in the preparation of graphene.…”
Section: Surface Engineering Of Catalytic Substrates For Graphene Growthmentioning
confidence: 99%